Development of the Biology Magazine on Virus as Teaching Materials for 10th Grade High School - Fauzi, Muhammad; Dewi, Asih Fitriana; Kapli, Hari (Al Jahiz, 2024)
The development of a biology magazine focused on viruses was motivated by students' lack of understanding of viruses and the lack of teaching materials for virus topics at Kartikatama Metro High School. The purpose of this research is to develop a biology magazine about viruses, analyze the validity of the developed product, and assess the responses of teachers and students to the product. The method used in this study is research and development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The test subjects in this study were a biology teacher and ten students from class X Science at Kartikatama Metro High School. The data analysis techniques used in this study include both quantitative and qualitative analysis. The data collection instruments consisted of an open-ended questionnaire for students and a closed-ended questionnaire for teachers. The product validation results indicated that the developed teaching materials were considered "highly valid" for testing, with 93% approval from material experts and 85% from media experts. Additionally, the trial responses to the product were rated as "very good," with a 97.7% response rate from the teachers and 97.4% from the students.